2021
DOI: 10.21608/amj.2021.196448
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Effect of Flaxseed Extract on Letrozole-Induced Polycystic Ovary Rat Model: Correlative Histological and Functional Study

Abstract: Background: Polycystic Ovary Syndrome (PCOS) is one of the most common metabolic disorders affecting women in the reproductive age leading to infertility/subfertility. It may occur as a complication of Letrozole (LTZ) therapy in breast cancer patients.Objective: This was a preliminary study to assess the possible protective and/or curative effect of flaxseed extract in a letrozole-induced PCO rat model. Material and Methods:Thirty-six adult female albino rats were divided into five main groups: Group I kept as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…The results of our current study showed a significant increase in the body weight of females treated with letrozole, and this result corresponds with the results of Jahan et al [23] who noticed a significant increase in the body weight of rats treated with letrozole at a dose of 1 mg / kg orally for a period of 21 days , and agree with the results of some authors [20] Those who recorded a significant increase in the weight of female rats treated with letrozole at a dose of 3 mg / kg orally for a period of 21 days, Perhaps the reason for the high body weight in our current study is that the letrozole treatment caused high blood glucose, which contributes to the development of insulin resistance [11,12]. In the group treated with letrozole, there was a a significant increase in the ovarian weight, and this result is corresponds with Mohamed and Fathy , 2021 [20]. Those who observed a significant increase in ovarian weight after administering letrozole 3 mg/kg orally for 21 days, and agree with Ibrahim et al [24] those who noticed a significant increase in the ovarian weights when using letrozole at a dose of 1 mg / kg orally for a period of 21 days, the results not agree with Kafali et al, who reported nonsignificant increase in ovarian weight after taking Letrozole at a dosage of 1 mg/kg orally for 21 days.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of our current study showed a significant increase in the body weight of females treated with letrozole, and this result corresponds with the results of Jahan et al [23] who noticed a significant increase in the body weight of rats treated with letrozole at a dose of 1 mg / kg orally for a period of 21 days , and agree with the results of some authors [20] Those who recorded a significant increase in the weight of female rats treated with letrozole at a dose of 3 mg / kg orally for a period of 21 days, Perhaps the reason for the high body weight in our current study is that the letrozole treatment caused high blood glucose, which contributes to the development of insulin resistance [11,12]. In the group treated with letrozole, there was a a significant increase in the ovarian weight, and this result is corresponds with Mohamed and Fathy , 2021 [20]. Those who observed a significant increase in ovarian weight after administering letrozole 3 mg/kg orally for 21 days, and agree with Ibrahim et al [24] those who noticed a significant increase in the ovarian weights when using letrozole at a dose of 1 mg / kg orally for a period of 21 days, the results not agree with Kafali et al, who reported nonsignificant increase in ovarian weight after taking Letrozole at a dosage of 1 mg/kg orally for 21 days.…”
Section: Discussionsupporting
confidence: 93%
“…The studies found that giving female rats consecutive doses of letrozole disrupted their estrous cycle [22] Furthermore, letrozole use causes a disruption in the secretion of hormones from the pituitary gland and the ovaries, resulting in polycystic ovary syndrome due to hypersecretion of androgens in the blood and ovaries [10]. The results of our current study showed a significant increase in the body weight of females treated with letrozole, and this result corresponds with the results of Jahan et al [23] who noticed a significant increase in the body weight of rats treated with letrozole at a dose of 1 mg / kg orally for a period of 21 days , and agree with the results of some authors [20] Those who recorded a significant increase in the weight of female rats treated with letrozole at a dose of 3 mg / kg orally for a period of 21 days, Perhaps the reason for the high body weight in our current study is that the letrozole treatment caused high blood glucose, which contributes to the development of insulin resistance [11,12]. In the group treated with letrozole, there was a a significant increase in the ovarian weight, and this result is corresponds with Mohamed and Fathy , 2021 [20].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Flaxseed oil has many health benefits as it has a proper balance of essential fatty acids such as αlinolenic acid (ALA); an omega-3 biological precursor, linoleic acid; an omega-6 fatty acid; and omega-9 fatty acids. Potassium, lecithin, magnesium, 6% mucilage, traces of cyanogenic glycoside linamarin (El-galil and Mohammed, 2021), and vitamins (A, B, D, and E) are present in flaxseed. Flaxseed also includes phytoactive chemicals such as phenolic compounds, terpenoids, pigments, and other naturally occurring antioxidants.…”
Section: Introductionmentioning
confidence: 99%